2019
DOI: 10.1128/jvi.02119-18
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Vaccine-Induced HIV-1 Neutralizing and Effector Antibody Responses in Rabbit and Rhesus Macaque Animal Models

Abstract: Studies in animal models are essential prerequisites for clinical trials of candidate HIV vaccines. Small animals, such as rabbits, are used to evaluate promising strategies prior to further immunogenicity and efficacy testing in nonhuman primates. Our goal was to determine how HIV-specific vaccine-elicited antibody responses, epitope specificity, and Fc-mediated functions in the rabbit model can predict those in the rhesus macaque (RM) model. Detailed comparisons of the HIV-1-specific IgG response were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 111 publications
1
36
1
Order By: Relevance
“…7 and 8). As reported by Pollara et al (49), there were no significant differences in ADCC activity against gp120-coated target cells or antibody-dependent cellular phagocytosis (ADCP) of HIV-1 virions between the two vaccination regimens.…”
Section: Figsupporting
confidence: 50%
“…7 and 8). As reported by Pollara et al (49), there were no significant differences in ADCC activity against gp120-coated target cells or antibody-dependent cellular phagocytosis (ADCP) of HIV-1 virions between the two vaccination regimens.…”
Section: Figsupporting
confidence: 50%
“…We identified similar peak phagocytosis activity (10 weeks), but intriguingly we noted enhanced phagocytosis in gB FL vaccinees at 20 weeks indicating more robust phagocytosis durability in this group (median %phagocytosing cells: FL = 10.1% vs. mRNA = 7.1%, p<0.01, Kruskal-Wallis + post hoc Mann-Whitney U test). Next, we assessed NK cell degranulation activity (CD107a upregulation) when vaccine-elicited antibodies are incubated with HCMV-infected cells ( Figure 5F ), which we previously identified to approximate antibody-dependent cellular cytotoxicity (ADCC) for rabbits [17]. However, we were unable to measure NK degranulation activity for the majority of animals, suggesting that antibodies mediating this non-neutralizing effector function are not a dominant response elicited by gB FL, gB ecto, or gB mRNA vaccines.…”
Section: Resultsmentioning
confidence: 99%
“…HCMV preclinical vaccine development is hindered by the fact that small animal models poorly represent host-pathogen biology and mechanisms of disease pathogenesis [26, 27]. We chose to test immunogenicity in rabbits because we previously demonstrated that vaccination can elicit antibodies with both neutralizing and non-neutralizing in vitro functionality [17]. In this study we were able to epitope-map and define the function of antibodies elicited by these three experimental vaccines, then compare to previously-reported immune correlates of protection (Nelson, Journal of Infectious Diseases , 2019, in press).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations